You can go home now : a novel - Elias, Michael (Harper an imprint of HarperCollinsPublishers, 2020)
Nina is a tough Queens detective with a series of cold case homicides on her desk--men whose widows had the same alibi: they were living in Artemis, a battered women's shelter, when their husbands were killed. Nina goes undercover into Artemis. Though she is playing the victim, she's anything but. Nina knows about violence and the bullies who rely on it because she's experienced it in her own life. For the women living in Artemis there is no absolute moral compass--there is the law and there is survival. And, for Nina, who became a cop so she could find the man who murdered her father, there is only revenge.